Du colportage au musée du Louvre. Les mouleurs italiens en France au tournant du xixe siècle - Pauline Carminati (Diasporas: Circulations, Migrations, Histoire)
During the second half of 18th century a significant number of Italian plaster cast makers, mostly from Tuscany, arrived in France and they worked in itinerant and sedentary ways. In the first case, they traveled across the country peddling plaster statuettes of various subjects, reflecting the tastes of the moment or the place. In the second case, they were self-employed in large cities and developed a multipurpose activity in relation to artists and connoisseurs.